Genomic legacy of the African cheetah, Acinonyx jubatus. Issue 1 (December 2015) - Dobrynin, Pavel; Liu, Shiping; Tamazian, Gaik; Xiong, Zijun; Yurchenko, Andrey; Krasheninnikova, Ksenia; Kliver, Sergey; Schmidt-Küntzel, Anne; Koepfli, Klaus-Peter; Johnson, Warren; Kuderna, Lukas; García-Pérez, Raquel; et al.
Abstract Background Patterns of genetic and genomic variance are informative in inferring population history for human, model species and endangered populations. Results Here the genome sequence of wild-born African cheetahs reveals extreme genomic depletion in SNV incidence, SNV density, SNVs of coding genes, MHC class I and II genes, and mitochondrial DNA SNVs. Cheetah genomes are on average 95 % homozygous compared to the genomes of the outbred domestic cat (24.08 % homozygous), Virunga Mountain Gorilla (78.12 %), inbred Abyssinian cat (62.63 %), Tasmanian devil, domestic dog and other mammalian species. Demographic estimators impute two ancestral population bottlenecks: one >100, 000 years ago coincident with cheetah migrations out of the Americas and into Eurasia and Africa, and a second 11, 084–12, 589 years ago in Africa coincident with late Pleistocene large mammal extinctions. MHC class I gene loss and dramatic reduction in functional diversity of MHC genes would explain why cheetahs ablate skin graft rejection among unrelated individuals. Significant excess of non-synonymous mutations inAKAP4 (p <0.02), a gene mediating spermatozoon development, indicates cheetah fixation of five function-damaging amino acid variants distinct fromAKAP4 homologues of other Felidae or mammals;AKAP4 dysfunction may cause the cheetah's extremely high (>80 %) pleiomorphic sperm. Conclusions The study provides an unprecedented genomic perspective for the rare cheetah, with potential relevance to the species' natural history, physiological adaptations and unique reproductive disposition.